RETRACTED: Improving the country’s food security in the conditions of developing a circular economy - Uktamov Khusniddin; Akhmedov Sherzod; Khashimova Dilyora; Fayziyeva Khamida; Narmanov Ulugbek; Sobirova Dildora; Kuryozov Orinboy; Komilov Akhmadjon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001